PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA FLIPBOOK TERHADAP HASIL BELAJAR MURID PADA MATERI BAGIAN-BAGIAN BUMI DI KELAS V SDN 1 KABILA - Musa, Nur Anisah S.; Gamar Abdullah; Meylan Saleh; Kudus; Nurfadliah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research problem addressed in this study is: "Is there an effect of the Problem-Based Learning (PBL) model assisted by flipbook media on students’ learning outcomes in the topic of Earth's structure in Grade V at SDN 1 Kabila?" This study aims to determine the effect of the PBL model supported by flipbook media on students’ learning outcomes in the topic of Earth's structure. This research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The population consisted of all fifth-grade students, with a sample of 20 students. Data were collected through observation, tests, and documentation as supporting data. The results showed that the average pretest score was 38.5, while the average posttest score was 87. A comparison of these results indicates that the posttest average score is significantly higher than the pretest average score. Hypothesis testing was conducted using SPSS version 25.0, revealing that t_calculated = 14.176 > t_table = 1.725, or based on the significance value, sig = 0.000 < α = 0.05. Therefore, it can be concluded that the Problem-Based Learning model assisted by flipbook media has a significant effect on students’ learning outcomes in the topic of Earth's structure in Grade V at SDN 1 Kabila.